Diário da Saúde: sistema de registro de evoluções diárias com comunicação Bluetooth - Queiroz, Isadora Santarém de (Brasil, 2023)
Recording medical measurements is an essential and everyday part of the patient follow-up process, especially for the elderly. However, this monitoring is often done manually by professionals in the field as doctors, nurses, and caregivers. Thus, the main objective of this work is to implement a system for the control and storage of an emphasized measure for better management of records. Performing the quantitative method with a form with open and closed questions to obtain the basis for initial definitions of this work. With this north, the system had a division between hardware, with the assembly of an electronic device, and software, with an application for graphical presentation and recording of the collected data.